The impact of German unification on West Germany's goods and labor market: A macroeconometric disequilibrium model in action - Wolfgang Franz; Gustav W. Heidbrink; Werner Smolny (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1993)
This paper constitutes an interim report on the development of a macroeconometric disequilibrium model. Despite several caveats the model as it stands can be used already for two purposes. First, it is possible to investigate the models forecasting abilities. While the estimation period of the model ends in 1989, the forecast is made for the time period 1990 to 1993: This time period includes two events which form a real challenge to every macroeconometric model, namely German unification and the most severe recession afterwards. Secondly, the model is used to quantify selected impacts of unification on some macroeconomic variables with an exclusive emphasis on the goods and labor market. By and large, the results are in line with intuition. West Germany benefitted from unification by experiencing higher output and employment and so did major trade partners.
Keywords: 330; Ökonometrisches Makromodell; Wirtschaftswachstum; Arbeitsmarkt; Nationale Einheit; Deutschland